Policymaking and the politics of change in higher education: The new 1960s universities in the UK, then and now. (18th April 2016) - Filippakou, Ourania; Tapper, Ted
Abstract : Through an analysis of the foundation of the so-called 'new universities' in the UK, this article offers an interpretation of the change process in higher education. The argument is that although change is driven by economic and social forces, it is the political interpretation of these forces that steers the change process and, therefore, determines the shape of new institutional structures and how they are supposed to perform their tasks. The article contrasts the original steering of the change process by state and quasi-state institutions with the more recent emergence of state-regulated market pressure as the force for change in higher education.